1999
DOI: 10.2527/1999.7761547x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IGF binding proteins in bovine milk and the demonstration of IGFBP-3 synthesis and release by bovine mammary epithelial cells.

Abstract: Insulin-like growth factor system components are synthesized and secreted by mammary epithelial cells and multiple IGF binding proteins (IGFBP) are found in milk of various species. This study was conducted to identify the IGFBP in bovine milk, to compare them with those found in blood, and to identify the cell(s) responsible for mammary IGFBP synthesis. Bovine blood, milk, and cell culture-conditioned media were analyzed and characterized with Western ligand blot procedures for specific IGFBP. Electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…A similar observation was reported in bovines by Gibson et al (1999). It has also been suggested that, although IGFBP-5 appear in milk, leakage or biotransport of IGFBP-5 from blood to milk may have happened during the pre-colostrum period leading to an increase in its concentration (Gibson et al, 1999). Vega et al (1991) have reported that high concentrations of IGFBP-5 during the colostrum period may be due to the accumulation of IGF and IGFBP in the pre-colostral milk, 2 to 4 weeks prepartum.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A similar observation was reported in bovines by Gibson et al (1999). It has also been suggested that, although IGFBP-5 appear in milk, leakage or biotransport of IGFBP-5 from blood to milk may have happened during the pre-colostrum period leading to an increase in its concentration (Gibson et al, 1999). Vega et al (1991) have reported that high concentrations of IGFBP-5 during the colostrum period may be due to the accumulation of IGF and IGFBP in the pre-colostral milk, 2 to 4 weeks prepartum.…”
Section: Discussionsupporting
confidence: 89%
“…A comparatively higher concentration of IGFBP-5 during the colostrum period in present study may be due to the accumulation of IGFBP-5 in the mammary gland as a result of pre-parturient accumulation of milk ensuing parturition. A similar observation was reported in bovines by Gibson et al (1999). It has also been suggested that, although IGFBP-5 appear in milk, leakage or biotransport of IGFBP-5 from blood to milk may have happened during the pre-colostrum period leading to an increase in its concentration (Gibson et al, 1999).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations